(untitled) (Nativa, 2019)
A escassez de água doce é uma das principais preocupações do século XXI. As últimas projeções do IPCC preveem que para a região do Centro-Oeste deve ocorrer aumento da área agriculturável, diminuição das áreas florestais, aumento de temperatura e alteração da frequência e magnitude de cheias e de períodos de estiagem. Essas alterações afetam profundamente o ciclo hidrológico e por consequência a disponibilidade de água para consumo humano. No verão de 2016/2017 o Distrito Federal registrou a maior crise hídrica de sua história onde o volume do reservatório responsável pelo abastecimento de mais da metade da população ficou abaixo de 10%. Nesse sentido o presente estudo teve como principal objetivo trazer informações atualizadas sobre Pagamento por Serviços Ambientais, como um importante instrumento mitigador de mudanças climáticas, redutor de processos de alteração do uso do solo, sugerindo-o como instrumento para promover melhorias no abastecimento de água da Bacia do Descoberto. Palavras-chave: mudanças climáticas; gestão hídrica; serviços ecossistêmicos. PAYMENT FOR ENVIRONMENTAL SERVICES: AN INSTRUMENT OF MITIGATION OF THE EFFECTS OF CLIMATE CHANGE AND A MANAGEMENT TOOL FOR HYDRICAL CRISIS IN THE ALTO DESCOBERTO WATERSHED ABSTRACT: Freshwater shortages are one of the main concerns of the 21st century. The latest projections by the Intergovernmental Panel on Climate Change (IPCC) foresee that for the brazilian midwest, there should be an increase in the area planted to agriculture, a decrease in forest areas, an increase in temperature and a change in the frequency and magnitude of floods and droughts. These changes profoundly affect the hydrological cycle and consequently the availability of water for human consumption. In the summer of 2016/2017, the Federal District had the greatest water crisis in its history, where the volume of the reservoir responsible for supplying more than half the population was below 10%. In this sense, the main objective of the present study was to provide updated information on payment for environmental services as an important instrument to mitigate climate change, reducing soil use change processes, and suggesting it as an instrument to promote improvements in water supply in the Descoberto watershed. Keywords: climate change; water management; ecosystem services.